A comparison of the 1-year surgical outcomes of ab externo trabeculotomy and microhook ab interno trabeculotomy using propensity score analysis. Issue 1 (5th March 2020) - Mori, Sotaro; Murai, Yusuke; Ueda, Kaori; Sakamoto, Mari; Kurimoto, Takuji; Yamada-Nakanishi, Yuko; Nakamura, Makoto
Abstract : Objective: To compare the 1-year outcomes of trabeculotomy ab externo ( ab externo TLO) and trabeculotomy ab interno using a microhook ( ab interno TLO) for glaucoma patients using propensity score analysis. Methods and analysis: The medical charts of 65 consecutive patients who underwent ab externo TLO and those of 69 patients who underwent ab interno TLO were reviewed. Logistic regression analysis was conducted to calculate the propensity score using 1:1 matched analysis, which indicates the likelihood of surgical success at 12 months. We set the outcome-related covariates as age, glaucoma type, mean deviation, preoperative intraocular pressure (IOP), the number of preoperative glaucoma eye drops and the presence or absence of combined cataract surgery. Fifty eyes per each surgery group were subsequently compared. Results: The mean preoperative IOP was 32.5±11.2 mm Hg in the ab externo TLO group and 28.4±7.8 mm Hg in the ab interno TLO group (p=0.08). The mean postoperative IOP at 12 months was 18.3±7.4 mm Hg in the former group and 17.8±6.3 mm Hg in the latter (p=0.91). When surgical success was defined as a postoperative IOP of between 5 and 21 mm Hg with a more than 20% IOP reduction from baseline and no additional glaucoma surgery, the rate at 12 months was 78% in the ab externo TLO group and 74% in the ab interno TLO group (p=1.00). Conclusion: The 1-year success rate was not significantly different between ab externo and ab interno TLO.